PENINGKATAN KEMAMPUAN SANTRI MEMBACA AL- QUR’AN MELALUI PENDEKATAN ILMU TAJWID BUKU STANDAR TAJWID BACAAN AL-QUR’AN KARANGAN MAFTUH BASTHUL BIRRI (Studi Di Pondok Pesantren Ittihadut Tholibin Wonosobo) - Siti Muamanah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
The purpose of this research is to know the increasing extent of the students’ ability in reading Al- Qur’an recitation book science approaches through Standard Tajwid Qur’an Recitation By Maftuh Basthul Birri, who studied in Boarding schools Ittihadut Tholibin Wonosobo. The research was held in boarding schools IItihadut Tholibin Wonosobo District Mojotengah, Wonosobo Regency with the subjects of the research are all existing students is 110 resondents. This is descriptive qualitative research methods i. e revealing symptoms af holistically- contextually through data collection from natural background by utilizing self researchers as the key instruments. The data collection methods used observation, interview, question form, documentation and analysis of the data by these steps: reduction of data, display data, conclusion and withdrawal (verification). The results of the research gained the ability of reading Al- qur’an boarding schools Ittihadut Tholibin Wonosobo is still lacking, i.e. from a level of SMP 53.3%, SMA 51,4%, college46, 7%. Then the upgrading of reading Al- Qur’an in boarding schools Ittihadut Tholibin Wonosobo can be categorized well,i.e. the level SMP 63%, SMA 63,3%, and college 66,7%. Conclusion of the research through the science of tajwid, the book approaches the standard Tajwid Qur’an Recitation by Maftuh Basthul Birri ITB students experience is increasing, i.e. the level of SMP 80%, SMA 80%, and College 82,2%.